Isolated cerebral metastasis of a triceps muscle leiomyosarcoma: A case report. (June 2014) - Gautschi, Oliver P.; Hottinger, Andreas F.; Lobrinus, Johannes A.; Schaller, Karl; Bijlenga, Philippe
Abstract Leiomyosarcomas are rare malignant neoplasms. Intracranial metastases of this tumour are even less frequently observed and have mostly been described from uterine leiomyosarcomas. In this article, we describe the case of a single right frontal subcortical cerebral metastasis in a patient with a right triceps muscle leiomyosarcoma. A right-sided frontal craniotomy with macroscopically complete tumour removal was performed, followed by combined radio-chemotherapy. The patient died 10 months after the initial diagnosis of the intracranial metastasis due to systemic tumour progression, without any evidence of intracranial recurrence.